Ethanolic extract of Coccinia grandis prevented glucose intolerance, hyperlipidemia and oxidative stress in high fat diet fed rats - Shahnaz Siddiqua; Faiza Hamid Jyoti; Nadia Saffoon; Pintu Miah; Soumen Lasker; Hemayet Hossain; Raushanara Akter; Md. Iqbal Ahmed; Md Ashraful Alam (Elsevier, 2021)
Background: Coccinia grandis (L.) Voigt (Cucurbitaceae) is well known as ivy gourd/little gourd in English, found to be beneficial in the management of diabetes. Purpose: This project was conducted to evaluate the beneficial effects of chemically characterized C. grandis ethanol extract in high fat (HF) diet fed rats. Methods: Antidiabetic test was performed by oral glucose tolerance test, antioxidant evaluation was done by the assessment of the antioxidants, anti-oxidant enzyme activity as well as liver marker enzymes activities in the plasma and tissues collected from the rats. Cholesterol level was also quantified in rats used in different groups. To monitor the fibrosis in the liver and infiltration of inflammatory cells, histological staining was performed. Results: C. grandis treatment significantly reduced cholesterol level, liver wet weight and peritoneal as well as epididymal fat accumulation in HF diet fed rats. Furthermore, C. grandis treatment significantly prevented the rise of liver enzymes and MPO activities in rats fed with HF diet. C. grandis treatment also successfully restored the activities of antioxidant enzymes in rats fed with HF diet. The outcomes for antioxidant potential specify that at both doses of C. grandis extracts (100 and 200 mg/kg) significantly prevented the oxidative stress parameters which are comparable to the standard metformin. Moreover, ethanolic extracts of C. grandis prevented inflammation or fibrosis in liver of HF diet fed rats. HPLC-DAD analysis of the extract identified and quantified significant number of phenolic compounds such as gallic acid, kaempferol and quercetin hydrate. Conclusion: This study suggests that, ethanolic extract of C. grandis can prevent fat deposition, hyperlipidemia, glucose intolerance and oxidative stress in rats fed with HF diet.